Sistem Manajemen Kehadiran Menggunakan Metode Face Recognition Berbasis Web - Nur Jaini; Ervan Asri; Fitri Nova (SOTVI - Society of Visual Informatics, 2021)
Attendance system with the use of face recognition is a system that utilizes biometrics in the form of facial patterns and compares detected faces with stored faces.To capture facial patterns from users who will be absent, use an esp32-cam camera module embedded in the face recognition library so that able to compare detected faces with stored ones. This system is integrated with a web server which is designed to manage and store student absences so that one face detection tool can be used by more than one class simultaneously. The web server is controlled by the admin to manage absent schedules starting from class schedules, class schedules as well as entry and exit hours, so that the use of the web server does not allow duplicate data or attendance more than once